Cryopreserved Amniotic Membrane in The Management of Persistent Epithelial Defect - Rajiv Garg; Siddharth Madan (Delhi Journal of Ophthalmology)
Amniotic membrane has anti-inflammatory, anti-scarring and anti-angiogenic properties. Preclinical and clinical evidence support the successful use of cryopreserved amniotic membrane in treating corneal epithelial defects and ulcers caused by neurotrophic keratitis and the ulcers which are unresponsive to prior treatment. The case describes one such use of amniotic membrane in the treatment of a persistent epithelial defect.